Destruction of the brush border by Salmonella enterica sv. Typhimurium subverts resorption by polarized epithelial cells - Felipe-López, Alfonso; Hansmeier, Nicole; Hensel, Michael (Frontiers in Microbiology, 2024)
Salmonella enterica serovar Typhimurium is an invasive, facultative intracellular gastrointestinal pathogen that destroys the brush border of polarized epithelial cells (PEC). The brush border is critical for functions of PEC, because it resorbs nutrients from intestinal lumen, and builds a physical barrier to infecting pathogens. We demonstrate that destruction of the brush border by Salmonella significantly reduces the resorption surface of PEC, which was accompanied by abrogation of endocytosis at the apical side of PEC. Both changes in the physiology of PEC were associated with translocation of type III secretion system effector protein SopE. Additionally, the F-actin polymerization rate at the apical side of PEC was highly altered by SopE, indicated that reduced endocytosis observed in infected PEC is related to manipulation of F-actin polymerization mediated by SopE, and to lesser extend by effectors SopE2 or SipA. We further observed that in absence of SopE, Salmonella effaced microvilli and induced reticular F-actin by bacterial accumulation during prolonged infection periods. In contrast to strains translocating SopE, strains lacking SopE did not alter resorption by PEC. Finally, we observed that after engulfment of Salmonella, ezrin was lost from the apical side of PEC and found later in early endosomes containing Salmonella. Our observations suggest that destruction of the brush border by Salmonella may contribute to pathogenesis of diarrhoea.